Reworking postcolonialism : globalization, labour and rights - Malreddy, Pavan Kumar, 1977-; Heidemann, Birte; Laursen, Ole Birk; Wilson, Janet, 1948- (Palgrave Macmillan, 2015)
"An interdisciplinary collection of essays, Reworking Postcolonialism explores questions of work, precarity, migration, minority and Indigenous rights in relation to contemporary globalization. It focuses on the impact of the global market forces on the formation of new subject positions among urban dwellers, exiles, and other disenfranchised communities. Bringing together political, economic and literary approaches to texts and events from across the postcolonial world, the essays collected here investigate the transformative effects of the global dissemination of capital, goods and movements of people, and call for a revision of the existing discourses on rights, entitlements and citizenship"--